Feasibility of using normobaric hypoxic stress in mTBI research. (22nd August 2017) - Regan, Patrick M; Bleiberg, Joseph; Onge, Paul St; Temme, Leonard
Studies of mild traumatic brain injury (mTBI) recovery generally assess patients in unstressed conditions that permit compensation for impairments through increased effort expenditure. This possibility may explain why a subgroup of individuals report persistent mTBI symptoms yet perform normally on objective assessment. Accordingly, the development and utilization of stress paradigms may be effective for enhancing the sensitivity of mTBI assessment. Previous studies, discussed here, indirectly but plausibly support the use of normobaric hypoxia as a stressor in uncovering latent mTBI symptoms due to the overlapping symptomatology induced by both normobaric hypoxia and mTBI. Limited studies by our group and others further support this plausibility through proof-of-concept demonstrations that hypoxia reversibly induces disproportionately severe impairments of oculomotor, pupillometric, cognitive and autonomic function in mTBI individuals.